GADAI SYARIAH LAHAN PRODUKTIF (Studi Kasus Di Desa Prancak Kecamatan Pasongsongan Kabupaten Sumenep) - Fadllan, Fadllan (STAIN PAMEKASAN, 2016)
This article is derived from 2 (two) research focuses, they are: firstly, how is the system of syariah pawning/security of productive land at Prancak village, Pasongsongan district, Sumenep regency? Secondly, how is the legal status of syariah pawning of productive land at Prancak village, Pasongsongan district, Sumenep regency from the perspective of syariah economy? The research result shows that (1) the pawning practice, done in at Prancak village, Pasongsongan district, Sumenep regency, has been completed from person to person (personal relationship) to help each other. The form of credit has been converted into value of things (gold and fertilizer) to protect and anticipate the value of credits form inflation since there is no time limitation during the transaction. This is considered as legal practice as far as it is not aimed at taking any advantages from murtahin side against the rahin side.Â (2) The legal status of syariah pawning of productive land at Prancak village, Pasongsongan district, Sumenep regency from the perspective of syariah economy has fulfilled the Islamic law. However, there remains imperfectness in the process of transaction because rahin does not provide the land certificate as the legal document toward the murtahin. From the view point of the use of syariah pawning of productive land at Prancak village, Pasongsongan district, Sumenep regency, it is cultivated by the rahin but it is collectively managed by both rahin and murtahin. The former is responsible for the cultivation and the latter is responsible for the operating cost, and there has been a profit sharing of the harvest. This practice is legal from the perspective of Islamic law since both sides are in mutual profit sharing and rahin is still able to function the pawning.